Effect of Cognitive Rehabilitation and Transcranial Direct Current Stimulation on Quality of Life and Subjective Vitality of the Elderly With Mild Cognitive Impairment - Fardin Farmani; Hossein Pourshahriar; Vahid Nejati; Omid Shokri (University of Social Welfare & Rehabilitation Sciences, 2023)
Objectives Quality of life and subjective vitality are two important components for the elderly. This study aims to study the effect of cognitive rehabilitation and transcranial direct current stimulation (tDCS) on the quality of life and subjective vitality of older adults with mild cognitive impairment (MCI). Methods & Materials This is a quasi-experimental study with a pre-test/post-test/follow-up design. The study population consists of all older adults referred to the Rehabilitation Clinic of Payambaran Hospital in Tehran and diagnosed with MCI based on clinical criteria. Of these, 40 were selected using a convenience sampling method and randomly assigned to two groups of intervention and control. For the intervention group, cognitive rehabilitation plus tDCS was provided at 12 sessions. The LEIPAD quality of life questionnaire and subjective vitality scale of Ryan and Frederick were used to measure the variables. Two-way repeated measures analysis of variance was used to analyze the data in SPSS software, version 25. Results There was a significant difference between the two groups in the quality of life and subjective vitality after intervention (P<0.05), indicating that the combination of cognitive rehabilitation with tDCS affected the quality of life and subjective vitality of the elderly. In the follow-up phase, the effects were stable over time. Conclusion Combining cognitive rehabilitation with tDCS can have a significant impact on the quality of life and subjective vitality of the elderly with MCI.